The Agonistic Objectification: Choreography as a play between abundance and lack. (3rd July 2016) - Petrović Lotina, Goran
Abstract : If a game refers to the contest between differential positions mobilized by contrasting interests, can we envisage a work of art in relation to a game structure? The answer is yes. All art is structured by the principles of game. All art is always about contesting one idea embodied in representation by another one that is excluded from it. This operation is reflected in the various ways that artistic practices—including performing arts—perceive and articulate everyday objects and the diverse ways that art theory tries to explain the being of these objects. But, to clarify this answer, let me explain what is at stake here. First, by offering a glimpse on Mette Edvardsen's choreographic work that examines the play between 'presence' and 'absence' of objects. And, second, by envisaging how contemporary performances contribute to the development of theory that reflects this play in the form of a game structured by means of contestation between philosophical trajectories of immanence and transcendence. What I am suggesting is that the insight into these theories and performance practices from the point of view of game structure will allow us to understand the political dimension of all social practice, including art and theory. In this regard, I will try to show that the political dimension of artistic practices is constituted in the eternal interplay, or encounter, of the two differential aspirations: one directed towards the ultimate grounding of the being of objects, and another directed towards the revelation of the historical, contingent and constructed nature of the being of objects. This view opens up the space for understanding the object in terms of agonistic rather than objective relations. The goal is to demonstrate that to acknowledge agonistic objectifications is to invigorate democracy.